Phylogeny and systematics of the genus Clonostachys - Wang, Yao; Tang, De-Xiang; Luo, Run; Wang, Yuan-Bing; Thanarut, Chinnapan; Dao, Van-Minh; Yu, Hong (Frontiers in Microbiology, 2023)
Clonostachys, a genus with rich morphological and ecological diversity in Bionectriaceae, has a wide distribution among diverse habitats. In the present study, a phylogenetic framework is reconstructed for the family Bionectriaceae focusing on Clonostachys through increased taxon-sampling using the nrLSU sequence. Through surveying Clonostachys in China, Vietnam, and Thailand over the past 3 years, seven Clonostachys spp. were found and identified. Two new species, C. chuyangsinensis and C. kunmingensis, are described and illustrated based on morphological characteristics and molecular data. The phylogenetic positions of the seven species were evaluated based on four genomic loci (ITS, nrLSU, TUB2, and TEF1). Moreover, the genetic divergence comparisons of Clonostachys species for three markers (ITS, TUB2, and TEF1) are also provided. The results indicated that the TEF1 sequence data provided the best resolution for distinguishing species of Clonostachys, followed by sequence data for the TUB2 and ITS regions.